ACQUISITION: IMPROVING BANK HEALTH AND CAPITAL STRENGTH IN RUNNING THE COMPANY - Hendra, Joni; Ulfah, Maria; Elma, Elma; Miranda, Mira Santika; Azriansyah, Azriansyah; Wulandari, Juliasti; Ardiansyah, M. Rifki (LPPM Univ. Ibn Khaldun Bogor, 2026)
This study examines bank acquisition as a strategy to strengthen competitive positioning, enhance capital structure, and support business expansion. An acquisition involves not only the integration of management systems, technology, and human resources, but also influences operational efficiency, asset optimization, and the improvement of banking services and products. Positive impacts are reflected in financial ratios, credit risk-bearing capacity, long-term growth, and operational stability, which help increase the trust of customers and other stakeholders. This study also highlights the importance of proper risk management and compliance with OJK regulations to ensure the sustainability and competitiveness of banks within an increasingly competitive banking industry.